2013
DOI: 10.1177/0142723713511000
|View full text |Cite
|
Sign up to set email alerts
|

The development of narrative productivity, syntactic complexity, referential cohesion and event content in four- to eight-year-old Finnish children

Abstract: This study focuses on the development of narrative structure and the relationship between narrative productivity and event content. A total of 172 Finnish children aged between four and eight participated. Their picture-elicited narrations were analysed for productivity, syntactic complexity, referential cohesion and event content. Each measure showed a developmental trend. Concerning consecutive age groups, significant differences were observed between four- and five-year-olds in productivity and event conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
52
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 32 publications
13
52
0
6
Order By: Relevance
“…Development of social-pragmatic abilities is accompanied by development of various cognitive and language abilities (see Perkins, 2007Perkins, , 2011. With increasing age children are more capable of managing inferential chains of different complexities (Bosco et al, 2013;Bosco & Gabbatore, 2017a, 2017bHarris & Pexman, 2003), express complex issues explicitly (Mäkinen, Loukusa, Nieminen, Leinonen, & Kunnari, 2014) and reason about beliefs (Heiphetz et al, 2013). In this study, we found the most significant progress in children's social-pragmatic abilities occurred between four and six years of age, which is also the period when children's ToM and other cognitive skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Development of social-pragmatic abilities is accompanied by development of various cognitive and language abilities (see Perkins, 2007Perkins, , 2011. With increasing age children are more capable of managing inferential chains of different complexities (Bosco et al, 2013;Bosco & Gabbatore, 2017a, 2017bHarris & Pexman, 2003), express complex issues explicitly (Mäkinen, Loukusa, Nieminen, Leinonen, & Kunnari, 2014) and reason about beliefs (Heiphetz et al, 2013). In this study, we found the most significant progress in children's social-pragmatic abilities occurred between four and six years of age, which is also the period when children's ToM and other cognitive skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies on TD children have indicated, from preschool years through middle-childhood, children's narrative skills undergo substantial developments in measures of referential cohesion, narrative structure, global coherence, and the use of connectives (Colozzo & Whitely, 2014;Gamannossi & Pinto, 2014;Mäkinen, Loukusa, Nieminen, Leinonen, & Kunnari, 2014;Peterson & McCabe, 1988). To gain insights into the narrative abilities in Mandarin-speaking children with ASD, therefore, investigations with school-age children should also be the focus for further research.…”
Section: Narrative Coherence In Mandarin-speaking Children With Asdmentioning
confidence: 99%
“…Or, alternatively, mental state talk development might have been constrained by children's narrative competence. Past studies on narrative competence development have emphasized that at 5 years of age, children storytelling skills are still limited and do not increase much before the onset of schooling [47,48]. For instance, they provide some details on the characters' thoughts and goals [49] but do not elaborate much about the characters' mental states or problem complications [50].…”
Section: Discussionmentioning
confidence: 99%